Language Learning Strategies (LLS) Instruction to Help Students Become Better Language Learners - Ernomo, Zandi (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
Based on act of The Republic of Indonesia number 20, year 2003 on National Education System, learners should be active participants and able to develop their full potential. From the statement, the paradigm in educational field has changed from teacher centered learning to student-centered learning. Teaching language learners to learn so that they will be effective learners is a major issue in language teaching nowadays. A way to do that is by conducting strategy instruction. So, the purpose of this paper is to find out the definition of LLS, factors affecting the choice of LLS, classification of LLS, characteristics of LLS instruction, and models of LLS instruction.